The financial effect of ‘Beetles’ on Big Web Technologies Limited - Ullah, Mohammad Muqtadir (BRAC University, 2017)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2017.